Fluctuations in dietary crude protein content affect rumen bacterial community and metabolome in Holstein dairy cows - Zhang, Chuankai; Liu, Yifan; Wang, Jiaying; Xing, Landan; Liu, Lei; Quan, Yingkai; He, Liukuan; Zhang, Liyang; Gao, Tengyun; Fu, Tong; Liu, Kaizhen; Lian, Hongxia (Frontiers in Veterinary Science, 2025)
IntroductionTo elucidate the effects of fluctuating dietary crude protein (CP) on Holstein dairy cows, this study investigated lactation performance, rumen bacterial communities, and metabolome profiles.MethodsIn a 60-day trial, twenty-four Holstein cows were randomly assigned to a fluctuating CP diet (FCP), high CP diet (HCP, 18.05% CP), or intermediate CP diet (ICP, 16.05% CP). FCP alternated between high (18.05%, FCP-HCP) and low CP (14.04%, FCP-LCP) every 48 h, forming a 96-h cycle. During the final cycle, blood, milk, and urine samples were collected to measure plasma urea nitrogen (PUN), milk urea nitrogen (MUN), and urine urea nitrogen (UUN). Rumen bacterial diversity and metabolomic profiles were also analyzed.ResultsFluctuating CP did not significantly affect lactation performance (p > 0.05). PUN in FCP was lower than HCP on Day 1 (p < 0.01), while MUN in ICP was lower than HCP and FCP on Day 2 (p < 0.01). On Day 3, PUN and UUN in FCP exceeded HCP and ICP (p < 0.05), and on Day 4, PUN in FCP was again lower than HCP (p < 0.01). FCP had lower Proteobacteria on Day 2 (p < 0.05) and lower Patescibacteria on Days 3–4 (p < 0.05). Metabolomics indicated shifts mainly in amino acid, energy, purine, and pyrimidine metabolism.DiscussionThese findings show that short-term CP fluctuations induce dynamic changes in nitrogen excretion, rumen bacterial composition, and key metabolic pathways without affecting milk production. This suggests that dietary CP variation primarily influences nitrogen metabolism and rumen bacterial dynamics rather than lactation performance.